2013
DOI: 10.1111/j.1365-3164.2012.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐31: its role in canine pruritus and naturally occurring canine atopic dermatitis

Abstract: Background -Interleukin-31 (IL-31) is a member of the gp130 ⁄ interleukin-6 cytokine family that is produced by cell types such as T helper 2 lymphocytes and cutaneous lymphocyte antigen positive skin homing T cells. When overexpressed in transgenic mice, IL-31 induces severe pruritus, alopecia and skin lesions. In humans, IL-31 serum levels correlate with the severity of atopic dermatitis in adults and children.Hypothesis ⁄ Objective -To determine the role of IL-31 in canine pruritus and naturally occurring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 16 publications
1
68
0
1
Order By: Relevance
“…IL-31-driven signaling has been shown to regulate a wide range of biological functions, including itch, induction of proinflammatory cytokines, regulation of cell proliferation, and tissue remodeling [3, 6, 7]. Previous studies have shown that IL-31 induces pruritus and severe dermatitis, and also regulates other allergic diseases that are characterized by these skin disorders [1, 8, 9]. Overexpression or administration of recombinant mouse IL-31 (rIL-31) in mice triggered a skin phenotype that in many ways resembled atopic dermatitis (AD) [1].…”
Section: Introductionmentioning
confidence: 99%
“…IL-31-driven signaling has been shown to regulate a wide range of biological functions, including itch, induction of proinflammatory cytokines, regulation of cell proliferation, and tissue remodeling [3, 6, 7]. Previous studies have shown that IL-31 induces pruritus and severe dermatitis, and also regulates other allergic diseases that are characterized by these skin disorders [1, 8, 9]. Overexpression or administration of recombinant mouse IL-31 (rIL-31) in mice triggered a skin phenotype that in many ways resembled atopic dermatitis (AD) [1].…”
Section: Introductionmentioning
confidence: 99%
“…IL-31 mRNA is significantly up-regulated in serum and skin of patients with pruritic atopic dermatitis [39;141;147]. Canine IL-31 was also detected in the majority of dogs with naturally occurring atopic dermatitis and intradermal injection of it induced pruritic behaviors in dogs [46]. Higher levels of blood β-endorphin and IL-31 significantly correlated itch severity in atopic dermatitis patients [83].…”
Section: Mechanisms Of Chronic Itchmentioning
confidence: 99%
“…When overexpressed in transgenic mice, IL-31 induces a pruritic skin condition that resembles human atopic dermatitis (Dillon et al, 2004). Importantly, T H 2 cells overproduce IL-31 in both canine (Gonzales et al, 2013) and human (Sonkoly et al, 2006) atopic dermatitis. A large subset of sensory neurons that coexpress TRPV1 with TRPA1 carry a receptor for IL-31 ; indeed, the IL-31-induced pruritus is ameliorated in both TRPV1-and TRPA1-deficient mice.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…IL-31 produced by T H 2 cells evokes itch when injected into the skin of mice (Dillon et al, 2004) or dogs (Gonzales et al, 2013). Several lines of experimental evidence point to IL-31 as a critical neuroimmune link between pathogenic T cells and pruriceptive afferents.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%